Creative Art Therapy for Improving Depression, Anxiety, and Stress in Patients with Stroke: A Quasi-Interventional Study - Khadeja Alwledat MSN, RN; Rasmieh Al-Amer PhD, MSN, RN; Amira Mohammed Ali PhD, MSN, RN; Yacoub Abuzied PhD, MSN, RN; Feras Adnan Khudeir MD; Naif S. Alzahrani PhD, MSN, RN; Saleh R. Alshammari BSN, RN; Mohammed AlBashtawy PhD, MSN, RN; Thanuja Thananayagam MD; Mahlagha Dehghan PhD, MSN, RN (SAGE Open Nursing, 2023)
Introduction Creative art therapy is a psychotherapeutic approach used to enhance the mental health status of patients. Objectives This study aimed to evaluate the effect of creative art therapy on the levels of depression, anxiety, and stress in Jordanian patients following stroke. Methods One-group pretest–posttest design was used; it included four sessions of creative art therapy which were conducted as two sessions for two weeks. This study recruited 85 participants who were within three months poststroke diagnosis. The Depression, Anxiety, and Stress Scale was used to assess the levels of psychological reactions pre and post creative art therapy intervention. Results The data showed that there was a statistically significant improvement in the levels of depression ( t  = 37.98; p < .001), anxiety ( t  = 20.59, p  < .001), and stress ( t  = 35.52, p  < .001) post-intervention. There was a statistically significant improvement in the study-related psychological aspects following creative art therapy. Conclusion The findings of this study suggest that creative art therapy is a valuable method to complement other types of treatments among patients with stroke, resulting in positive patient mental health outcomes. Creative art therapy could be used as a psychotherapeutic approach to manage mental health complexities among patients with stroke. Health policymakers are invited to use the findings of this study to establish tailored counselor services using this new psychotherapeutic approach.